2001
DOI: 10.1038/35079114
|View full text |Cite
|
Sign up to set email alerts
|

A frameshift mutation in NOD2 associated with susceptibility to Crohn's disease

Abstract: Crohn's disease is a chronic inflammatory disorder of the gastrointestinal tract, which is thought to result from the effect of environmental factors in a genetically predisposed host. A gene location in the pericentromeric region of chromosome 16, IBD1, that contributes to susceptibility to Crohn's disease has been established through multiple linkage studies, but the specific gene(s) has not been identified. NOD2, a gene that encodes a protein with homology to plant disease resistance gene products is locate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

57
3,038
5
71

Year Published

2001
2001
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 4,528 publications
(3,171 citation statements)
references
References 21 publications
57
3,038
5
71
Order By: Relevance
“…In addition, the recent identification of CARD15, a gene involved in NFkB activation as a susceptibility gene for CD, emphasizes the important role of the innate immune system in the pathogenesis of CD. 22,23 Although the data from the present study did not reveal a significant association with the IL-12 p40 TaqI polymorphism, this does not necessarily exclude a role for the IL-12 gene in the susceptibility to CD. The relatively small sample size in combination with the rare frequency of the variant allele may not have been powerful enough to detect such an association.…”
Section: Discussioncontrasting
confidence: 83%
“…In addition, the recent identification of CARD15, a gene involved in NFkB activation as a susceptibility gene for CD, emphasizes the important role of the innate immune system in the pathogenesis of CD. 22,23 Although the data from the present study did not reveal a significant association with the IL-12 p40 TaqI polymorphism, this does not necessarily exclude a role for the IL-12 gene in the susceptibility to CD. The relatively small sample size in combination with the rare frequency of the variant allele may not have been powerful enough to detect such an association.…”
Section: Discussioncontrasting
confidence: 83%
“…[1][2][3][4] The incidence of IBD is relatively higher in Caucasian than in Asian populations; however, the incidence in Asia is increasing. 5,6 Of the two types of IBD, the genetic contribution to disease risk has been documented more extensively and clearly for CD [7][8][9][10][11][12][13][14][15][16][17] than for UC. [18][19][20][21] So far, linkage and genome-wide association studies have identified more than 30 CD-susceptibility loci in Caucasian populations.…”
Section: Introductionmentioning
confidence: 99%
“…An allele of murine TLR4, Lpsd, was first noted to decrease the severity of experimental colitis induced by dextran sulfate sodium (DSS), 6 and more recently, TLR4 À/À and MyD88 À/À mice have been shown to have more severe DSS-induced colitis than their wild-type littermates. [7][8][9] In addition, mutations in CARD15/NOD2 have been associated with susceptibility to human CD [10][11][12] and shown to affect nuclear factor-kB (NF-kB) activation, interleukin (IL)-1b processing, and resistance to intestinal Listeria monocytogenes infection in mice. 13,14 Within the TLR family of PRR, there are 10 different transmembrane receptors (TLR1-10) that are found either on the extracellular surface of cells (TLR1, 2 and 4) or within intracellular compartments such as endosomes (TLR3 and 7-9).…”
Section: Introductionmentioning
confidence: 99%